Origins of the university museums of Peru. Foundational managements, tensions and motivations - Hurtado Castro, Hernán Iván (2022)
The new global museological trends, such as ecomuseums, digital museums, community museums, among others, also have an impact on the design and execution of university museums and their management of collections, that is, a permanent institutional tension, be it economic, infrastructure, of management, of specialization, of its very conception and of its function as it corresponds to the role of the university in / with society.Thus, this text tries to be a genealogical site of the university museum in Peru, from a review of the tensions and foundational motivations of some cases of museums in relation to the ownership of their universities, and the transition to contemporary museum institutions. Therefore, in the institutional process within the foundation and development of the republic and with the idea of nation, institutional designs, behaviors and images are also imported or provided in the conception of a museum supervised by an institution of higher education, this it is, in other words, a university museum.